2015
DOI: 10.1063/1.4913734
|View full text |Cite|
|
Sign up to set email alerts
|

The total position-spread tensor: Spin partition

Abstract: The Total Position Spread (TPS) tensor, defined as the second moment cumulant of the position operator, is a key quantity to describe the mobility of electrons in a molecule or an extended system. In the present investigation, the partition of the TPS tensor according to spin variables is derived and discussed. It is shown that, while the spin-summed TPS gives information on charge mobility, the spin-partitioned TPS tensor becomes a powerful tool that provides information about spin fluctuations. The case of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…The general formalism of the spin-partitioned TPS tensor is fully unfolded in our previous works on the H 2 molecule 16 and hydrogen chains. 25 In the present paper, we summarize its main aspects and describe its application to the special case of Heisenberg chains.…”
Section: The Spin Partition Of Tps Tensor For the Heisenberg Wavmentioning
confidence: 99%
See 2 more Smart Citations
“…The general formalism of the spin-partitioned TPS tensor is fully unfolded in our previous works on the H 2 molecule 16 and hydrogen chains. 25 In the present paper, we summarize its main aspects and describe its application to the special case of Heisenberg chains.…”
Section: The Spin Partition Of Tps Tensor For the Heisenberg Wavmentioning
confidence: 99%
“…The TPS presents important properties for molecules such as size-consistency 11,12 which is crucial to describe bond breaking and chemical processes. 8,[13][14][15][16] Hence, given that it encloses information about the overall wave function, the TPS is particularly appropriate to study finite-size systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible applications of PST to the chemical bonding in molecules were given in Refs. . An important contribution was also been made by Ángyán and coworker who attempted to relate several known chemical localization descriptors to the density response function and to construct spatially resolved analog of PST.…”
Section: Introductionmentioning
confidence: 99%
“…Even a spin resolved version has also been studied. 30 It has been shown that the TPS is very sensitive to bond stretching, becoming large in the case of increased electron mobility. In simple diatomics, for instance, its parallel component is small at equilibrium, it increases as the interatomic distance is enlarged before achieving a maximum value close to the bond breaking region, and it decreases again towards the free atomic value at dissociation.…”
Section: The Localization Tensor In Finite Moleculesmentioning
confidence: 99%